1983
DOI: 10.1007/bf01805472
|View full text |Cite
|
Sign up to set email alerts
|

Cystinosis in the Federal Republic of Germany. Coordination and analysis of the data

Abstract: In our survey, 101 infants and children with cystinosis were registered in the Federal Republic of Germany. Ninety-five patients showed the infantile type of cystinosis, five the adolescent type and one possibly the adult type. The minimum incidence rate of infantile and adolescent cystinosis in the FRG was 1 patient per 179 000 live-births. In contrast to other countries, cystinotic patients were evenly distributed in the FRG. Patients with cystinosis originated more frequently from rural communities than fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…More than 20 years ago, patients died from uncontrolled water and electrolyte disturbances, as well as from uremia. 26,32 Renal complications are improved by cysteamine. Cysteamine makes it possible to delay the occurrence of ESRD if therapy is introduced before the age of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 years ago, patients died from uncontrolled water and electrolyte disturbances, as well as from uremia. 26,32 Renal complications are improved by cysteamine. Cysteamine makes it possible to delay the occurrence of ESRD if therapy is introduced before the age of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide birth prevalence data concerning cystinosis are only reported in few populations. The overall incidence rates reported in France [ 9 ], Australia [ 10 ], Germany [ 11 ], Denmark [ 12 ] and Sweden [ 13 ] were 1:167,000, 1: 192,000, 1: 179,000, 1:115,000 and 1:260,000 live births, respectively. Higher incidence rate is observed in selected populations with detected founder mutations as in the province of Brittany, France (1:26,000 live births) [ 14 ] or in the Saguenay-Lac-St-Jean, Quebec, Canada (1:62,500 live births) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cystine-depletion therapy with cysteamine allows significant improvement in life expectancy [ 14 , 18 ], but cannot prevent the development of CKD and other systemic complications, and needs to be continued after kidney transplantation [ 7 ]. Recent data have demonstrated that lysosomal cystine accumulation is not the only pathological event related to the absence of functional cystinosin [ 19 ], which might explain why treatment with cysteamine is not curative.…”
Section: Introductionmentioning
confidence: 99%